Religious Diversity: An Islamic Perspective - Zia-ul-Haq, Muhammad (Islamic Studies, 2010)
The present study aims to overview the teachings of Islam about the concept of religious diversity and pluralism. The study proceeds from a brief description of the notion of religious pluralism and its importance in contemporary world. Then the place of other faiths in Islam, the Islamic concept of Prophet-hood and its link with the chain of Prophets are discussed. The theological basis of the relationship of Islam with other religions, particularly with Christianity and Judaism, are analyzed in the third part of the study. Following this, the discussions by Muslim scholars on the validity of previous revelations for the Muslims are explored. The next part discusses the status of non-Muslim individuals in Islamic states. This discussion aims to clarify some misconceptions regarding the status of the non-Muslim citizens in Muslim countries and elaborates how this status was extended to other people apart from the Christians and the Jews. A discussion on the Islamic point of view regarding the freedom of faith and its significance in interfaith relations constitutes the last part of the study. Suggestions regarding the importance of religious diversity in the Islamic faith and its utilization in the post-9/11 world setting are presented in the conclusion.